Enhancement of maximum temperature drop across thermoelectric cooler through two-stage design and transient supercooling effect. (1st August 2016) - Lv, Hao; Wang, Xiao-Dong; Meng, Jing-Hui; Wang, Tian-Hu; Yan, Wei-Mon
Highlights: A new design concept is proposed to enhance the maximum temperature drop across TECs. The design combines cascade TEC with transient supercooling effect. Effectiveness of the design is verified by a multiphysics and transient TEC model. Pulse parameters and TEC geometry are examined to further improve supercooling. Abstract: In this work, a new design concept which combines two-stage design with transient supercooling effect is proposed to enhance the maximum temperature drop across thermoelectric coolers (TECs). A three-dimensional, multiphysics, and transient model is used to examine the design effectiveness. Step current pulses with various amplitudes ( P ) and widths ( τ ) are supplied to the two stages of a two-stage TEC in series. The results show that, as compared with the single-stage counterpart, a significant improvement in the maximum cold-end temperature drop (Δ Tc, max ) is observed for the two-stage TEC. Meanwhile, the new design also greatly reduces the temperature overshoot ( Tc, max ) and increases the holding time of supercooling state (Δ t hold ). Subsequently, effects of the pulse amplitude, width, and shape are discussed and two important geometry parameters: the cross-sectional area ratio of p -type leg to n -type leg and the leg length ratio of cold stage to hot stage are investigated. These results confirm that Δ Tc, max, Tc, max, and Δ t hold can be further improved by optimizing the pulse and the geometry parameters. This work provides a feasible cooling approach for some specific cooling targets, such as mid-infrared laser gas sensors or any other semiconductor devices which require a temporary but large temperature drop.